78.0k views
5 votes
Show step to solve 3(t+4)-2(2t+3)=-4

2 Answers

2 votes

Answer: t = 10

Explanation:

Reorder the terms:

12 + 3t + -2(3 + 2t) = -4

12 + 3t + (3 * -2 + 2t * -2) = -4

12 + 3t + (-6 + -4t) = -4

Reorder the terms:

12 + -6 + 3t + -4t = -4

Combine like terms: 12 + -6 = 6

6 + 3t + -4t = -4

Combine like terms: 3t + -4t = -1t

6 + -1t = -4

Solving

6 + -1t = -4

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6' to each side of the equation.

6 + -6 + -1t = -4 + -6

Combine like terms: 6 + -6 = 0

0 + -1t = -4 + -6

-1t = -4 + -6

Combine like terms: -4 + -6 = -10

-1t = -10

Divide each side by '-1'.

t = 10

Simplifying

t = 10

User Jonathan Gleason
by
5.9k points
5 votes

Answer:

t=10

Explanation:

3*(t+4)-2*(2*t+3)-(-4)=0

Step by step solution :

Step 1 :

Equation at the end of step 1 :

((3 • (t + 4)) - 2 • (2t + 3)) - -4 = 0

Step 2 :

Equation at the end of step 2 :

(3 • (t + 4) - 2 • (2t + 3)) - -4 = 0

Step 3 :

Equation at the end of step 3 :

10 - t = 0

Step 4 :

Solving a Single Variable Equation :

4.1 Solve : -t+10 = 0

Subtract 10 from both sides of the equation :

-t = -10

Multiply both sides of the equation by (-1) : t = 10

User Kongsea
by
5.4k points